Relict geomorphological and structural control on the coastal sediment partitioning, North of Bay of Biscay - David Menier, Guilhem Estournès, Manoj Joseph Mathew, Muthuvaira, . (2016)
From the Glénan Island to Guérande plateau in south Brittany (France, Bay of Biscay), based on 10000 km of seismic lines, submerged rocky barriers/inherited structural elements were interpreted as the primary controls on variance of coastal topography and incision of palaeovalleys. Sediment infilling is regulated by valley morphology and fluctuation of energy conditions since the last marine transgression associated with the opening of the sea which in turn is a function of climate warming and sea level rising.